Penyusunan Direktori Insan Ombudsman Republik Indonesia Tahun 2020 - Damaji Ratmono (Universitas Wijaya Kusuma Surabaya, 2022)
Intoduction. This paper raises the theme of the process of creating the 2021 edition of the Human Ombudsman Directory of the Republic of Indonesia. Research Purpose. The purpose of this paper is to design and produce a printed directory in an effort to find information about employee data at the Ombudsman. Research Methode. The research method used is a descriptive method with data collection techniques in this case data regarding the 2020 Ombudsman Ranking List (ORL) through the Human Resources and General Bureau, Secretariat General of the Indonesian Ombudsman. Results and Discussions. Based on the data analysis, it can be concluded that the preparation of the directory is through the following steps: 1) collecting data; 2) record data; 3) focus on ideas; 4) create a book outline so that writing is directed; 5) write a directory concept; 6) determine the subject; 7) classifying or grouping data; 8) create directory elements according to the data; 9) designing the directory model; 10) create an index of employee names; 11) make covers. Conclusions. After all these processes are complete, the directory can be printed and reproduced so that it is hoped that the printed directory that has been created can easily search for the information needed and can be used as an effort to optimize information sources.Keywords: Directory, Human Ombudsman, Ombudsman of the Republic of Indonesia